The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fimmu.2019.00081
|View full text |Cite
|
Sign up to set email alerts
|

HIV Impacts CD34+ Progenitors Involved in T-Cell Differentiation During Coculture With Mouse Stromal OP9-DL1 Cells

Abstract: HIV-1 causes the loss of CD4+ T cells via depletion or impairment of their production. The latter involves infection of thymocytes, but the involvement of hematopoietic CD34+ cells remains unclear even though HIV-positive patients frequently manifest myelosuppression. In order to have a closer look at the impact of HIV-1 on T-lineage differentiation, this study utilized the OP9-DL1 coculture system, which supports in vitro T-lineage differentiation of human hematopoietic stem/progenitor cells. In the newly dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…These results suggest that the CXCR4-tropic HIV-1 strain may affect the differentiation rate or death rate of CD34 + CD7 + lymphoid progenitor cells, resulting in impaired T-cell production capacity. 33 and HSCs from INRs is much lower than that the colony-forming ability of those from IRs. 39 These studies suggest that incomplete immune reconstitution in HIV-1-infected individuals may be associated with impaired bone marrow hematopoietic function and decreased proliferative capacity.…”
Section: Bone Marrow and Hematopoietic Progenitor Cellsmentioning
confidence: 77%
See 1 more Smart Citation
“…These results suggest that the CXCR4-tropic HIV-1 strain may affect the differentiation rate or death rate of CD34 + CD7 + lymphoid progenitor cells, resulting in impaired T-cell production capacity. 33 and HSCs from INRs is much lower than that the colony-forming ability of those from IRs. 39 These studies suggest that incomplete immune reconstitution in HIV-1-infected individuals may be associated with impaired bone marrow hematopoietic function and decreased proliferative capacity.…”
Section: Bone Marrow and Hematopoietic Progenitor Cellsmentioning
confidence: 77%
“…utilized the in vitro OP9‐DL1/HIV‐1 model, cocultured cord‐derived CD34 + HPCs and CXCR4‐tropic HIV‐1 NL4‐3, and showed that CD34 + CD7 + CXCR4 + cells were rapidly depleted 1 week after HIV‐1 infection, accompanied by dramatically diminished numbers of CD34 + CD7 + CD4 + cells. These results suggest that the CXCR4‐tropic HIV‐1 strain may affect the differentiation rate or death rate of CD34 + CD7 + lymphoid progenitor cells, resulting in impaired T‐cell production capacity . Li et al.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 96%
“…Also, in a macaque model, following challenge with simian immunodeficiency virus, BMderived CD34 + cells exhibited reduced T-lineage differentiation potential in vitro without significant changes in phenotypic analysis of CD34 + subsets (Thiebot et al, 2005). Another recent study suggested that CD34 + CD7 + CXCR4 + cells may be depleted in response to CXCR4-tropic HIV-1 infection in a coculture of HIV-infected umbilical cord-derived CD34 + and OP9-DL1 cells (Tsukamoto, 2019b ; Figure 1). Despite the evidence of LPs during HIV-1 infection, our understanding of the impact of HIV-1 on LPs remains limited.…”
Section: The Impact Of Hiv On T-lineage Developmentmentioning
confidence: 93%
“…[5,40] The majority of studies that have investigated the ability of HIV to infect HSPCs are laboratory-based. [40][41][42]47,48] Due to ethical and logistical challenges related to obtaining sufficient volumes of bone marrow aspirate from HIV-infected individuals, patient (ex vivo)-based studies are scarce. In an isolated study, Redd et al [40] reported that HIV-1 subtype C (HIV-1C), but not HIV-1 subtype B (HIV-1B), has the potential to infect HSCs.…”
Section: Direct Infection Of Hspcsmentioning
confidence: 99%